Production of nitrogen-based platform chemical: cyanophycin biosynthesis using recombinant Escherichia coli - Zhang, Yixing (Kansas State University, 2010)
Synthesis of chemical derivatives from finite fossil fuels requires considerable energy inputs and leaves an undesirable environmental footprint. The emerging biorefinery approach leads to sustainable processing of biomass into a wide spectrum of bio-based products, catering to food, feed, chemicals, materials, and bioenergy industries. Cyanophycin (multi-L-arginyl-poly-L-aspartic acid, CGP) is a non-ribosomally synthesized reserve polypeptide, which consists of equimolar amounts of arginine and aspartic acid arranged as a polyaspartate backbone and arginine as the side chain. Cyanophycin is a source of the constituent N-functionalized platform chemical, which can be further processed into many other chemicals of importance. It can be hydrolyzed in mild condition to its constituent amino acids - aspartic acid and arginine. These amino acids may be utilized directly in food and pharmaceutical applications. Based on the chemical structure of these amino acids and the presence of functionalized nitrogen-containing groups, it is conceivable that a number of industrial chemicals can be synthesized, for example: 1, 4-butanediamine， a co-monomer in the production of nylon-4, 6. Other chemicals which could be obtained from cyanophcyin, that are currently prepared from fossil resources, include 1,4-butanediol and urea. Cyanophycin can also be hydrolyzed to a derivative with reduced arginine content or even to poly-aspartic acid, and used as a biodegradable substitute for synthetic polyacrylate in various technical process, such as water treatment (water softeners) and plastics. Cyanophycin is produced by most cyanobacteria in nature; however, these microbes are not suitable for large-scale production due to slow growth and low polymer content. Biosynthesis of cyanophycin is catalyzed by a single enzyme - cyanophycin synthetase (CphA), which is encoded by cyanophycin synthetase structure gene (cphA). The cphA gene can be expressed in several bacteria and plants. E.coli is one of the most commonly used bacterial hosts for the production of recombinant proteins. The recombinant culture has the ability to produce considerably large quantities of cyanophycin in a shorter period of time compared to cyanobacteria. Genome of Anabaena variabilis ATCC 29413 has been sequenced, and it contains the structural gene (cphA) for cyanophycin synthetase. The native enzyme-cyanophycin synthetase from this cyanbacterium culture had been purified and it consists of identical subunits of 98kDa. Polymerization of the amino acids to cyanophycin in vitro is dependent on the presence of ATP, K+, Mg2+, a (cyanophycin) primer and a thiol reagent such as β-mercaptoethanol in the reaction mixture. Our research is the first time that cphA gene from A. variabilis ATCC 29413 was cloned into E.coli. The 2.7 kb cphA gene was amplified by PCR, ligated to the vector pET45b+ and cloned into BL21 (DE3) pLysS and BL21 (DE3). Characterization of cyanophycin was performed by SDS-PAGE, HPLC, mass spectrometry and amino acid analysis. Results showed that protein with molecular weight of 21.5 to 31 kDa did not match any E.coli proteins when compared with E.coli protein data base, thereby showing expression of a protein foreign to host strain. Amino acids analyses showed that the cyanophycin produced by recombinant E.coli contained aspartic acid and arginine, and small amount of lysine, in the ratio: 1.05: 1: 0.2 (mass basis), thereby confirming cyanophycin biosynthesis. Experiments for high cyanophycin synthesis was performed at shake flask and 2-L fermentor level using recombinant BL21 (DE3) pLysS, LB broth as carbon and nutrient source, and casamino acids as primer. The maximum yield of cyanophycin obtained in flask level was 7.6% of cell dry mass, and the yield increased to 12.6% of cell dry mass at 2-L fermentor level. Cyanophycin is also referred to as “structural granules” because of substructures visible in electron micrographs. Phase contrast photomicrograph was able to depict cyanophycin inclusions in the cytoplasm, and transmission electron microscopy depicted finer details inside cell after IPTG induction.
Keywords: Cyanophycin; Platform chemical; Fermentation; Recombinant E.coli; Agriculture, General (0473); Biology, Molecular (0307)